The Economics of Reverse Osmosis Desalination Projects - Wilf, Mark; Semiat, Raphael (Journal of Membrane and Separation Technology, 2016)
Desalination applications based on reverse osmosis (RO) technology today comprise over 50% of the capacity of all desalination systems worldwide and represent 75-85% of new desalination projects being implemented. The major reason for the shift in desalination projects to RO technology is the high energy efficiency of the RO process. There are three major application categories of large capacity, RO-based desalination projects: brackish RO; advanced municipal wastewater reclamation; and seawater RO. In the two first categories (brackish RO and wastewater reclamation), the systems’ configuration and equipment components are well defined. Therefore, project costs and operating expenses are fairly predictable. In seawater RO desalination systems, the RO process configuration is also very similar; however, some variability exists regarding the configuration of seawater water delivery and feed water pretreatment. The rest of the system’s components and system operation methods are very uniform. However, an evaluation of published cost data of medium- to large-scale water RO desalination projects illustrates significant variability in costs of desalination systems. This paper will analyze current economic conditions of seawater desalination, and highlight the limitations and possibilities of additional improvements of the economics of the SWRO desalination process.